PluriBAC: A Versatile Baculovirus-Based Modular System to Express Heterologous Genes in Different Biotechnological Platforms - Amorós Morales, Leslie Cinthya (2023)
Baculoviruses are insect-specific pathogens widely used in biotechnology. In particular,the Autographa californica nucleopolyhedrovirus (AcMNPV) has been exploited as a platform forbio-inputs production. This is why the improvement of the technologies used for the productionof recombinant baculoviruses takes on particular relevance. To achieve this goal, we developed ahighly versatile baculoviral transfer vector generation system called PluriBAC. The PluriBAC systemconsists of three insert entry levels using Golden Gate assembly technology. The wide availability ofvectors and sticky ends allows enough versatility to combine more than four different promoters,genes of interest, and terminator sequences. Here, we report not only the rational design of thePluriBAC system but also its use for the generation of baculoviral reporter vectors applied to differentfields of biotechnology. We demonstrated that recombinant AcMNPV baculoviruses generated withthe PluriBAC system were capable of infecting Spodoptera frugiperda larvae. On the other hand,we found that the recombinant budded virions (BV) generated using our system were capable oftransducing different types of tumor and normal cells both in vitro and in vivo. Our findings suggestthat the PluriBAC system could constitute a versatile tool for the generation of insecticide and genetherapy vectors.